Mekanisme Koping Pada Penderita Diabetes Mellitus Yang Kontrol Rutin Di Poli Penyakit Dalam RSUD Dr. Soegiri Lamongan: Qualitative Fenomenologis Research - Devi Hijratur Rohmah, - (2012)
Coping mechanism was an individual effort to deal with a stressor. Diabetes mellitus was a degenerative disease that could not be cured and could become a stressor for the patients. If this stressor unhandled it can make the condition of patients become worse. The object of this research was to know the coping mechanism of diabetic person. This study was qualitative phenomenology research which used in-depth interview. The population in this research was the diabetic patient who routine control in internal division RSUD Dr. Soegiri Lamongan. This research was using purposive sampling with five people as the samples. The recording result of interview would be transcribed as the data. Data would be classified depend on the criteria inclusion and would be analyzed by reduction, data serving, and data conclution to get the good result. The results showed that interviews with partisipants indicated they have accepted their condition by making efforts to deal with negative feelings experienced through self control, taking a positive appraisal and accepting the responsibility. They tended able to do a good self-management to deal with diabetes mellitus by performing the routine control, dietary changes, looking for information about diabetes mellitus and exercise regularly. Partisipants were also getting support from family, friends, and health professionals. It conclude that coping mechanisms were performed by diabetic person include emotional focused coping to deal with negative emotions and problem focused coping to deal with diabetes itself through management regimen task. Therefore, the nurse should also asses the emotional needs of the patients found the coping mechanism that patients do. Moreover nurse can determine an effective intervention for patients with diabetes mellitus. Keywords: coping mechanism, diabetes mellitus, emotional focused coping, problem focused coping.